An fMRI investigation of expectation violation in magic tricks - Danek, Amory H.; Öllinger, Michael; Fraps, Thomas; Grothe, Benedikt; Flanagin, Virginia L. (Frontiers in Psychology, 2015)
Magic tricks violate the expected causal relationships that form an implicit belief system about what is possible in the world around us. Observing a magic effect seemingly invalidates our implicit assumptions about what action causes which outcome. We aimed at identifying the neural correlates of such expectation violations by contrasting 24 video clips of magic tricks with 24 control clips in which the expected action-outcome relationship is upheld. Using fMRI, we measured the brain activity of 25 normal volunteers while they watched the clips in the scanner. Additionally, we measured the professional magician who had performed the magic tricks under the assumption that, in contrast to naïve observers, the magician himself would not perceive his own magic tricks as an expectation violation. As the main effect of magic – control clips in the normal sample, we found higher activity for magic in the head of the caudate nucleus bilaterally, the left inferior frontal gyrus and the left anterior insula. As expected, the magician’s brain activity substantially differed from these results, with mainly parietal areas (supramarginal gyrus bilaterally) activated, supporting our hypothesis that he did not experience any expectation violation. These findings are in accordance with previous research that has implicated the head of the caudate nucleus in processing changes in the contingency between action and outcome, even in the absence of reward or feedback.